Comparison of the 2008 global financial crisis, 2015 stock market crash and COVID-19 pandemic: impacts on the consumer products and services sector of Malaysia using Pearson correlation - Dellow, Alyssa April; Abdul Razak, Fatimah; Ismail, Munira; Bahaludin, Hafizah (AIP Publishing, 2024)
The rise of unforeseen occurrences with severe consequences, commonly referred to as black swan events, have brought about sudden shocks to stock markets all around the world. The 2008 global financial crisis (GFC), 2015 stock market crash (SMC) in China and the Coronavirus disease 2019 (COVID-19) outbreak are examples of such events. Pearson correlation coefficient analysis can be executed to provide an initial overview of intricate stock market dynamics via stock closing price data. In this study, a comparison of the impacts of the three major events on the Consumer Products and Services sector of Bursa Malaysia is carried out. The 2008 GFC, 2015 SMC and COVID-19 pandemic financial market correlation matrices were built upon 134, 156 and 162 stocks respectively. Consequently, this study reveals that when the market is impacted by major events, the correlation structure of the financial market goes through changes in terms of direction and magnitude with differing patterns for each major event. Particularly, the impacts brought forth by COVID-19 are more drastic than that of the other two major events. Furthermore, the findings highlight the Malaysian stock market’s distinctiveness in that investors appear to like taking risks. It was also found that fluctuations in negative and positive correlation coefficients are a good indicator of triggering events taking place. This study is important to aid market regulators in administering policies to reduce systemic risk as well as to assist market participants in the management of their portfolio strategies.